Leadership in the Scientific View of Islamic Philosophy - Rahmatulloh, Aang; Inayatullah, Muhamad Iqbal; Purwanto, Purwanto; Dahlan, Charly; Pua, Fatmawati (Universitas Pahlawan Tuanku Tambusai, 2025)
In Islamic teachings, leadership is a sacred mandate from Allah that demands sincerity, honesty, justice, open-mindedness, and wisdom, with every leader ultimately accountable before Him. Leadership must begin with right intentions, seeking only Allah’s pleasure and viewing the role as a responsibility, not a privilege. The Prophet Muhammad taught that women should not hold the reins of leadership in certain contexts and warned against seeking positions for personal ambition, as leadership given upon request leaves one to bear the burden alone, whereas if bestowed without asking, Allah grants assistance. A leader must adhere strictly to Allah’s laws, judge fairly, and maintain justice, for injustice leads to ruin in the Hereafter. They should remain accessible to the people, keeping their doors open to needs and complaints, sincerely advising the community, and refusing gifts to avoid corruption. Surrounding oneself with righteous advisors is essential to promote good and prevent wrongdoing. Gentleness is highly valued in leadership, as the Prophet prayed for ease upon those who are kind to their people and hardship for those who are harsh. Leaders must not create suspicion or spy on the people, as this erodes trust and destroys society. The Prophet emphasized that every individual is a leader within their domain—a ruler over their people, a wife over her household, and a servant over their master’s trust—and each will be held responsible for those under their care. Thus, leadership in Islam is both an honor and a heavy trust that must be carried with integrity and fear of Allah.